Effects of Extruded-Expelled Soybean Meal and Benzoic Acid on Growth Performance, Carcass Characteristics, and Carcass Iodine Value of Finishing Pigs - Jenna J. Bromm; Joel M. DeRouchey; Mike D. Tokach; Kiah M. Berg; Jon A. De Jong; Courtney L. Pohlen; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,162 pigs (PIC 1050 × DNA 600; initially 69.2 ± 4.9 lb) were used in a 109-d finishing trial to evaluate the effects of extruded-expelled soybean meal (EESBM) and benzoic acid on growth performance, carcass characteristics, and carcass iodine value. Pigs were randomly allotted to 1 of 4 treatments with 27 to 28 pigs per pen and 20 pens per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of soybean meal source and benzoic acid. Diets contained either conventional soybean meal (SBM) or extruded-expelled soybean meal (EESBM; Lester Feed and Grain, Lester, IA) with or without 0.25% VevoVitall (DSM Products; Parsippany, NJ), a source of benzoic acid. The EESBM was analyzed to be 43.2% CP and 7.73% fat (acid hydrolysis). Experimental diets were not balanced for energy, but rather formulated to the same SID Lys:ME ratio and fed based on a feed budget from d 0 to 109 in 6 phases. Overall (d 0 to 109), there were no interactions between soybean meal source and benzoic acid addition. There was a main effect of soybean meal source where pigs fed conventional SBM had greater (P= 0.01) ADFI compared to pigs fed EESBM without influencing ADG, resulting in improved (P<0.001) F/G. Also, pigs fed diets without benzoic acid had greater (P= 0.02) ADFI compared to pigs fed diets that contained benzoic acid without influencing ADG, resulting in pigs fed benzoic acid having improved (P= 0.01) F/G. When evaluating caloric efficiency, pigs fed diets containing benzoic acid had improved (P<0.001) caloric efficiency compared to pigs fed diets without benzoic acid, with soybean meal source not having any impact. For carcass characteristics, pigs fed EESBM had increased (P<0.001) carcass fat iodine value compared to pigs fed conventional SBM. For economics, there was a main effect of soybean meal source where pigs fed EESBM had a higher (P≤ 0.002) feed cost per pig placed in the low and high feed cost scenarios. There were no differences in revenue per pig placed in the low or high revenue scenarios regardless of soybean meal source or the inclusion of benzoic acid. Pigs fed conventional SBM had a higher (P≤ 0.02) income over feed cost (IOFC) compared to pigs fed EESBM in the high feed cost, high revenue; high feed cost, low revenue; and low feed cost, low revenue scenarios. In summary, replacing conventional SBM with EESBM improved feed efficiency, but due to increased feed cost without influencing gain, it was less economical as measured by IOFC. Also, the addition of benzoic acid improved feed efficiency but did not improve IOFC.
Keywords: benzoic acid; carcass characteristics; extruded-expelled soybean meal; finishing pigs; growth performance; iodine value